2016
DOI: 10.1177/0958928716657278
|View full text |Cite
|
Sign up to set email alerts
|

When flexibility meets familialism: Two tales of gendered labour markets in Spain and South Korea

Abstract: Korea and Spain share crucial labour market and welfare state characteristics that converge to produce similar outcomes: strongly dualized labour markets, weak social protection, and features that are archetypical of familialist states. Labour market flexibility in both countries has recently increased through unusually high levels of temporary employment. Yet, when we analyse female labour force participation, we observe a significant divergence: Korean women interrupt their participation in the labour market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The Women's Political Power Index, which includes women's representation in ministries, parliaments, and regional assemblies, situated Spain well above the EU average as early as 2012 (EIGE 2012). This is line with previous research which has shown the positive impact of women's advocacy groups in the Spanish policy agenda and party system (León, Jun Choi and Jong-Soon 2016;Valiente 1996).…”
Section: Sourcesupporting
confidence: 93%
“…The Women's Political Power Index, which includes women's representation in ministries, parliaments, and regional assemblies, situated Spain well above the EU average as early as 2012 (EIGE 2012). This is line with previous research which has shown the positive impact of women's advocacy groups in the Spanish policy agenda and party system (León, Jun Choi and Jong-Soon 2016;Valiente 1996).…”
Section: Sourcesupporting
confidence: 93%
“…Job insecurity is associated with poor health and is generally higher in women than in men [ 28 , 29 ]. Furthermore, the labor market is highly gender-segmented in South Korea [ 30 , 31 ], as well as in other countries [ 30 , 32 ]. Whilst women work mainly in the caretaking, sales, and service sectors, men work mainly in the manufacturing sector [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crisis itself had a strong impact in Korea, leading to a spike in unemployment in the late 1990s, but this factor alone cannot explain the observed long-term changes in fertility. Similarly, the financial crisis did not lead to a long-term increase in the vulnerability of families with children: Rather, the initially very limited government spending on families and social protection has expanded since the late 1990s (e.g., León, Choi, and Ahn 2016;Sacchi and Roh 2016). These reforms included an extension of maternity leave, establishment of parental leave since 2001, and a vast expansion of public childcare provision, which is now fully financed by the government.…”
Section: Discussionmentioning
confidence: 99%
“…However, labor market opportunities for younger people, especially women, deteriorated after 1997, and this trend occurred in tandem with a stronger attachment of married women to employment. The Korean labor market has long been characterized by very long working hours, a male-oriented work culture, a huge gender pay gap -with women's average earnings amounting to 62% of male wages in 2014 (OECD 2017) -but also a very high share of female labor force in self-employment and high rates of 'nonregular' (temporary and nonstandard) work contracts (León, Choi, and Ahn 2016;Grubb, Lee, and Tergeist 2007;Ma 2013Ma , 2014.…”
Section: Discussionmentioning
confidence: 99%